2010
DOI: 10.1007/s10489-010-0244-1
|View full text |Cite
|
Sign up to set email alerts
|

A robust missing value imputation method for noisy data

Abstract: Missing data imputation is an important research topic in data mining. The impact of noise is seldom considered in previous works while real-world data often contain much noise. In this paper, we systematically investigate the impact of noise on imputation methods and propose a new imputation approach by introducing the mechanism of Group Method of Data Handling (GMDH) to deal with incomplete data with noise. The performance of four commonly used imputation methods is compared with ours, called RIBG (robust im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…As it can be seen, the RIBG estimates the missing values of individual matchers based on the behaviour of other matchers [2]. Future work will focus on addressing the issue of insufficient number of matchers in the multimodal identification system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As it can be seen, the RIBG estimates the missing values of individual matchers based on the behaviour of other matchers [2]. Future work will focus on addressing the issue of insufficient number of matchers in the multimodal identification system.…”
Section: Resultsmentioning
confidence: 99%
“…Missing information may be in the form of missing modalities in the template or the query or incomplete score information from individual matchers. Data reduction methods, which delete all incomplete vectors, are not suitable in such cases [2]. Imputation methods, on the other hand, which substitute the missing scores with predicted values are a better solution as (a) they do not delete any of the score vectors, which may contain useful information for identification, and (b) their application could be followed by a standard score fusion scheme.…”
Section: Introductionmentioning
confidence: 99%
“…The RIBG algorithm [2] is a recently proposed imputation approach. It is based on the Group Method of Data Handling (GMDH), which is applied in a great variety of areas for data mining and knowledge discovery, forecasting and systems modeling, optimization and pattern recognition.…”
Section: Ribg Algorithm Based Data Imputationmentioning
confidence: 99%
“…Comparative studies on 9 benchmark dataset from the UCI (University of California at Irvine) have shown that the RIBG algorithm outperforms other imputation techniques, including regression imputation, EM imputation, grey-based nearest neighbor imputation and multiple-imputation based on fully Not selected candidate models Selected candidate models conditional specification. We refer interested readers to [2] for a detailed description of the RIBG algorithm.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation